2011
DOI: 10.1111/j.1741-6787.2011.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Methods Evaluation Research for a Mental Health Screening and Referral Clinical Pathway

Abstract: This study provides an evaluated clinical pathway for generalist community nurses to screen for mental health difficulties, make appropriate referrals as required and to support war veteran and war widow clients. However, the study also shows how research can be used to develop and evaluate practical, evidence-based clinical pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Originally developed in English for use in the United States, these instruments have been translated to several other languages and extensively used in other settings as measures of nonspecial psychological distress and serious mental illness (SMI; see below) in epidemiologic studies (Aldworth et al, ; Arnaud et al, ; Carra et al, ; Donker et al, ; Fassaert et al, ; Han, Gfroerer, Colpe, Barker, & Colliver, ; Kessler et al, ; Kessler et al, ; Sakurai, Nishi, Kondo, Yanagida, & Kawakami, ). These measures have also been clinically used as screeners for establishing treatment referrals in PHC settings and for disability claimants (Allen et al, ; Cornelius, Groothoff, van der Klink, & Brouwer, ; Donker et al, ; Fassaert et al, ; Furukawa, Kessler, Slade, & Andrews, ; Kessler et al, ). We further compared the psychometric properties of these measures with the 12‐item General Health Questionnaire (GHQ‐12) that has been validated and extensively used in Iran (Bahremand et al, ; Emami, Ghazinour, Rezaeishiraz, & Richter, ; Heidari, Feizi, Roohafza, Hassanzadeh Keshteli, & Adibi, ; Montazeri et al, ) and other countries (Danielsson, Lundin, Allebeck, & Agardh, ; Diniz et al, ; Padron, Galan, & Rodriguez‐Artalejo, ; Pope et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Originally developed in English for use in the United States, these instruments have been translated to several other languages and extensively used in other settings as measures of nonspecial psychological distress and serious mental illness (SMI; see below) in epidemiologic studies (Aldworth et al, ; Arnaud et al, ; Carra et al, ; Donker et al, ; Fassaert et al, ; Han, Gfroerer, Colpe, Barker, & Colliver, ; Kessler et al, ; Kessler et al, ; Sakurai, Nishi, Kondo, Yanagida, & Kawakami, ). These measures have also been clinically used as screeners for establishing treatment referrals in PHC settings and for disability claimants (Allen et al, ; Cornelius, Groothoff, van der Klink, & Brouwer, ; Donker et al, ; Fassaert et al, ; Furukawa, Kessler, Slade, & Andrews, ; Kessler et al, ). We further compared the psychometric properties of these measures with the 12‐item General Health Questionnaire (GHQ‐12) that has been validated and extensively used in Iran (Bahremand et al, ; Emami, Ghazinour, Rezaeishiraz, & Richter, ; Heidari, Feizi, Roohafza, Hassanzadeh Keshteli, & Adibi, ; Montazeri et al, ) and other countries (Danielsson, Lundin, Allebeck, & Agardh, ; Diniz et al, ; Padron, Galan, & Rodriguez‐Artalejo, ; Pope et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In military health systems, military screening is a factor that facilitates timely diagnosis. [ 19 21 27 28 29 34 ] Therefore, in the community of veterans and soldiers who have completed their service, the routine screening system is an effective component in the operationalization of the veterans’ referral system. [ 21 34 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 14 21 30 ] The defined structure for the referral of veterans resolves the ambiguities of the service provider regarding the referred cases, and in cases of disagreement on the patient referral and the uncertainty of the doctors about the initial levels of referral, the defined clinical guidelines provide evidence-based decisions. [ 29 ]…”
Section: Resultsmentioning
confidence: 99%
“…14,15 Most studies reported that care pathway implementation was based on staff education. [16][17][18][19][20] In addition, the leader or manager was mentioned as the key for implementing care pathways. [17][18][19][20][21] Identifying leaders or mentors could help encourage care pathway implementation after formal education.…”
mentioning
confidence: 99%
“…Implementation strategies are poorly reported in the literature; hence, the best strategy for implementing a care pathway remains unclear 14,15. Most studies reported that care pathway implementation was based on staff education 16–20. In addition, the leader or manager was mentioned as the key for implementing care pathways 17–21.…”
mentioning
confidence: 99%